The Influence of The Informativeness of Tourist-Chatbot Interaction and Halal Facilities and Services on the Destination Image of Generation Z in Muslim-Friendly Tourism at Mount Bromo - Afra Bahita Fridajaya; Ririn Tri Ratnasari (Journal of Tourism Economics and Policy, 2026)
This study aims to analyze the influence of tourist-chatbot interaction informativeness and halal facilities and services on destination image among Generation Z in the context of Muslim-friendly tourism at Mount Bromo. A quantitative survey approach was employed by distributing online questionnaires to 224 Muslim Generation Z respondents selected through purposive sampling. The respondents were active users of ChatGPT and had an interest in Muslim-friendly tourism at Mount Bromo. The data were analyzed using multiple linear regression. The findings show that tourist-chatbot interaction informativeness has a positive and significant effect on destination image. Halal facilities and services also have a positive and significant effect on destination image. Simultaneously, both independent variables explain 60.8% of the variation in destination image. These results indicate that digital information quality through chatbot interaction and the availability of halal-oriented facilities are important factors in shaping a positive image of Muslim-friendly tourism destinations. The findings provide practical implications for destination managers to integrate reliable digital information services with halal facilities to improve destination competitiveness among Muslim Generation Z tourists.